A influéncia dos comportamentos de empatia e recomendação do terapeuta na interação terapeuta-cliente - Kanamota, Priscila Ferreira de Carvalho [UNESP]; Bolsoni-Silva, Alessandra Turini [UNESP]; Kanamota, Juliano Setsuo Violin (My University, 2016)
This study aims to verify the effects of the increased frequency of the empathetic response and therapist recommendation in therapist-patient interaction. The participants are 4 mothers/caregivers of adolescents with behavioral problems. A quasi single case experimental design composed of phases A (baseline), B (empathy) and C (recommendation) were utilized. Therapist and patient verbalizations were categorized utilizing the Multidimensional System for the Categorization of Behaviors in Therapeutic Interactions in all psychotherapeutic sessions and the Working Alliance Inventory was applied at the end of each phase. The results indicated that client’s verbalization of Solicitation and Concordance were facilitated during the Recommendation phase while complicating the Establishment of Relations verbalizations. In addition, a decrease in the scores of subcategory Objectives were observed during the Empathy phase.
The influence of empathetic behavior and therapist recommendation in therapist-patient interaction
Keywords: Empathy; Evidence-Based Psychology; Interaction Therapist-Patient; Recommendation; Therapeutic Relation